Chinese English as a Foreign Language Teachers’ Self-Efficacy and Psychological Well-Being as Predictors of Their Work Engagement - Kong, Xiansui (Frontiers in Psychology, 2021)
Work engagement is widely acknowledged as an influential element in teachers’ professional success; thus, remarkable attention has been paid to the physical and psychological predictors of this construct. Yet, the antecedents of English as a foreign language (EFL) teachers’ work engagement have rarely been studied. To narrow the existing gap, the current inquiry aimed to delve into the psychological determinants of teacher work engagement by scrutinizing the role of psychological well-being and self-efficacy in Chinese EFL teachers’ engagement. To this end, three close-ended questionnaires were given to 304 Chinese EFL teachers via WeChat messenger. Conducting correlational analyses, positive and substantial relationships were discovered between psychological well-being, self-efficacy, and teaching engagement. The function that psychological well-being and self-efficacy may serve in Chinese EFL teachers’ engagement was also assessed using path analysis. Chinese EFL teachers’ work engagement was found to be considerably affected by their sense of efficacy and well-being. Some pedagogical implications that might be noteworthy for teachers and institutional administrators are finally discussed.